Eksplorasi Professional Learning Community (PLC) pada Dimensi Supportive and Leadership di Sekolah Dasar Program Khusus - Ardhi, Muh. Waskito; Praptiwi, Erma; Ernawati, Dwi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
Supportive leadership in the teacher community in schools has an important meaning for the formation of professional learning communities. The purpose of this study was to explore the experiences of teachers involved in the application of PLCs which were limited to the dimensions of Supportive and shared leadership in Special Program-based primary schools. The research approach used case studies. The source of data in this study was 15 teachers in 2 special program elementary schools located in Boyolali district, Central Java, Indonesia. Data collection using semi-structured interviews. The data in this study was analyzed using thematic analysis techniques. The results of this study found that there are 11 themes that describe the dimensions of supportive and leadership, namely (1) types of leadership support (2) school leadership strategies (3) forms of teacher leadership (4) means of leadership guidance (5) forms of implementing decisions (6) leadership attitudes (7) evaluation of decision implementation (8) teacher collaboration (9) collaboration media (10) forms of teacher responsibility to the community and (11) leadership roles.